THE CORRUPTION OF POLITICS. Issue 2 (9th May 2019) - Philp, Mark
Abstract: This essay challenges conceptions of political corruption that rely on standards external to politics and explores an understanding of corruption as something that is part of the internal policing of politics. The essay draws attention to the multiple, conflicting ideas and principles that contribute to our understanding of corruption but argues that these often generate over-moralized and over-generalized claims and can become corrosive of the compromises and procedures that are central to political rule. The essay shows that recent accounts of political corruption often have highly attenuated understandings of "politics" and are over-expansive in their normative commitments, and argues that how we understand and talk about the corruption of politics is of major significance for the stability and effectiveness of the political orders of Western societies.